HUMAN CAPITAL, ORGANIZATIONAL COMMITMENT ON WORK MOTIVATION AND IMPLICATIONS TO EMPLOYEE PERFORMANCE - Indah, Dewi (Faculty of Economic and Business, University of Pasundan, 2024)
The purpose of this research is to determine the results of human capital, organizational commitment,work motivation and employee performance, to determine the magnitude of the influence of human capital, organizational commitment, on motivation and its implications for employee performance. The method used is descriptive and verification. Determining the sample in the research used the Slovin formula so that a sample of 104 respondents was obtained. Findings: result found human capital, organizational commitment, work motivation and employee performance were poor. And using Path Analysis, the results obtained show that there is an influence of human capital,and organizational commitment on motivation partially or simultaneously, as well as the influence of work motivation on employee performance.